2016
DOI: 10.1111/ijfs.13159
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilms in food processing environments: a review of recent developments in chemical and biological control

Abstract: Biofilms are immobile communities of micro-organisms attached to any surface, such as stainless steel or a food matrix surface or on packaging material. They may be composed of a single species, but more generally, in the natural environment, they consist of mixed species together with an extracellular matrix. Biofilms provide a common mechanism of persistence for a number of bacterial species especially in food processing environments, and therefore, prevention of biofilm formation and the removal of preforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 132 publications
2
26
0
2
Order By: Relevance
“…Plant extracts as well as pure plant‐derived compounds (mainly phenolic compounds) have received increasing attention as natural antimicrobial and antibiofilm agents against important foodborne pathogens in the recent years (Elhariry et al ., ; Phillips, ). Cranberry juice, elaborated from fruits of Vaccinium macrocarpon Ait., has also long been used to prevent infections of the urinary tract, which are often related to biofilm formation and numerous studies have found that A‐type proanthocyanidins (PACs) (oligomers with at least a double interflavanyl linkage between two flavan‐3‐ol units) from cranberries have antibiofilm properties against many bacterial and fungal pathogens (Rane et al ., ; Ulrey et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Plant extracts as well as pure plant‐derived compounds (mainly phenolic compounds) have received increasing attention as natural antimicrobial and antibiofilm agents against important foodborne pathogens in the recent years (Elhariry et al ., ; Phillips, ). Cranberry juice, elaborated from fruits of Vaccinium macrocarpon Ait., has also long been used to prevent infections of the urinary tract, which are often related to biofilm formation and numerous studies have found that A‐type proanthocyanidins (PACs) (oligomers with at least a double interflavanyl linkage between two flavan‐3‐ol units) from cranberries have antibiofilm properties against many bacterial and fungal pathogens (Rane et al ., ; Ulrey et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Among these, Escherichia coli O157:H7, Salmonella enterica serovars and Listeria monocytogenes have been the most frequently encountered bacterial pathogens in outbreaks on minimally processed produce and food (Phillips, 2016;Skerni skyt_ e et al, 2016). Among these, Escherichia coli O157:H7, Salmonella enterica serovars and Listeria monocytogenes have been the most frequently encountered bacterial pathogens in outbreaks on minimally processed produce and food (Phillips, 2016;Skerni skyt_ e et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces with biofilms of L. brevis did not show any positive reaction because this microorganism is catalase negative (Whittenbury, 1964) and no positive action was expected. In food industry environment, the non-detection of negative catalase microorganisms would not be a problem because biofilms are formed by mixed species (Colagiorgi et al, 2017;Elias & Banin, 2012;Phillips, 2016) and therefore the use of the biodetector would show microbial activity. Biofilms formed by mixed species constitutes a general adaptation of foodborne pathogens and microbiota associated to the food-processing environment for extended survival in their food niche (Jahid & Ha, 2014).…”
Section: Detection Of Biofilms Using Dem and The Different Biodetectomentioning
confidence: 99%